The Detection of Xanthate in Solution and on Sulfide Surfaces to Help Understand and Improve Mineral Separation on Industrial Plants - D Yan; R Dunne (The Australasian Institute of Mining and Metallurgy, 2005)
In flotation where a bulk flotation concentrate is produced or a gangue sulfide such as pyrite contaminates a concentrate, residual collector has to be removed from the sulfide surfaces to allow selective separation in a subsequent flotation step. Depending on the sulfide mineral, the main species that needs to be removed when using a xanthate collector is either a metal xanthate or dixanthogen. For the identification of surface species, specific solvents may be used to remove each species û metal xanthates are known to be soluble in acetone whilst dixanthogens are known to be soluble in non-polar solvents such as diethyl ether. Xanthates break down with time, temperature and pH into various decomposition products. The major decomposition product is dixanthogen which can aid flotation but other products such as perxanthate and carbon disulfide can have an adverse effect on flotation. Various analytical techniques can be employed to monitor the formation of decomposition products on the surface of the mineral and in solution. The best of these is ultraviolet spectroscopy as it has diagnostic peaks for decomposition product determination. In this work two approaches were taken to understand the relationship between the flotation of a chalcopyrite and pyrite from an ore containing these two minerals. One approach was to remove the xanthate species with an organic solvent and then use ultraviolet spectroscopy to determine the concentration of dissolved species. The second method involved measuring xanthate decomposition in solution by measuring the residual xanthate concentration using ultraviolet spectroscopy. These experiments confirmed the species adsorb at the surface of the mineral and how these species affect the recovery and grade of the valuable mineral. In both cases pH and temperature were varied and two xanthate collectors (SEX and PAX) were used to study these relationships. These relationships could be applied to industrial flotation systems and allow for more accurate determination of optimal xanthate dosage and hence save on reagent costs.